Studying in China: Analysis of the Implementation of Formative Assessment in Learning and its Contribution to Islamic Religious Education - Amiruddin; Khalid Hasan Minabari; Kusaeri; Fauziah Md. Jaafar (TADRIS: Jurnal Pendidikan Islam, 2025)
The education system in China is heavily influenced by Confucianism, which has led to an exam-oriented education system and a teacher-centered approach to learning. This environment is less conducive to the implementation of formative assessment, which emphasizes evaluating the learning process. However, this does not mean that process-based assessments are not applied in China. On the contrary, formative assessments are still used despite challenges from a system that prioritizes exam results. This article discusses the implementation, effectiveness, challenges of formative assessment in China, and contributions for Islamic Religious Education. The method used is a Systematic Literature Review (SLR) with the help of Prisma 2020. The results show that formative assessment in China is implemented through various methods such as student journals, portfolios, teacher-student interactions, formative tasks, self-assessment, peer assessment, classroom observation, and feedback. Formative assessment has proven effective in improving students’ academic performance. However, its implementation faces challenges at the macro level (national education policy), meso level (school management), and micro level (classroom practices). Several formative assessment practices in China that can be adapted for assessment in Islamic education include feedback, portfolios, formative tasks, self-assessment, and peer assessment.